Aortic valve replacement: validation of the Toronto Aortic Stenosis Quality of Life Questionnaire - Frank, Derk; Kennon, Simon; Bonaros, Nikolaos; Stastny, Lukas; Romano, Mauro; Lefèvre, Thierry; Di Mario, Carlo; Stefàno, Pierluigi; Ribichini, Flavio; Himbert, Dominique; Urena-Alcazar, Marina; Salgado-Fernandez, Jorge; et al. (ESC heart failure, 2021)
AIMS: There is no quality of life tool specifically developed for patients with severe aortic stenosis (AS) to assess how this chronic condition and its treatment affect patients. The Toronto Aortic Stenosis Quality of Life Questionnaire (TASQ) has been developed to overcome this gap. The results of the validation of the TASQ in patients undergoing treatment for severe AS are presented. METHODS AND RESULTS: Prospective study at 10 centres in Europe and Canada, which enrolled 274 patients with severe symptomatic AS undergoing surgical or transcatheter aortic valve replacement. Mean TASQ score at baseline was 71.2 points and increased to 88.9 three months after aortic valve implantation (P < 0.001). Increases were seen for the emotional impact (32.0 to 39.0; P < 0.001), physical limitations (14.8 to 22.0; P < 0.001), and physical symptoms (8.5 vs. 11.0; P < 0.001) domains. Internal consistency was good/excellent for overall TASQ score (α = 0.891) and for the physical limitation, emotional impact, and social limitation domains (α = 0.815-0.950). Test-retest reliability was excellent or strong for the overall TASQ (intraclass correlation coefficient of 0.883) and for the physical symptoms, physical limitation, emotional impact, and social limitation domains (intraclass correlation coefficient of 0.791-0.895). Responsiveness was medium overall (Cohen's d = 0.637) and medium/large for physical symptoms, emotional impact, and physical limitations (0.661-0.812). Sensitivity to change was significant for physical symptoms, physical limitations (both P < 0.001), emotional impact (P = 0.003), and social limitations (P = 0.038). CONCLUSIONS: The TASQ is a new, brief, self-administered, and clinically relevant health-specific tool to measure changes in quality of life in patients with AS undergoing an intervention.
Keywords: Surveys and Questionnaires; Questionnaire; aortální stenóza; Humans; Aortic valve replacement; Quality of Life; výsledek terapie; Aortic stenosis; lidé; Europe; Aortic Valve Stenosis; kvalita života; reprodukovatelnost výsledků; průzkumy a dotazníky; Canada; Kanada; Reproducibility of Results; Treatment Outcome; Quality of life; prospektivní studie; aortální chlopeň; Evropa; Aortic Valve; Prospective Studies